Application of high performance thin layer chromatography and fourier transform infrared profiling coupled with chemometrics for the differentiation of the varieties of ficus deltoidea jack - Khamsah Suryati, Mohd; Nashriyah, Mat; Azierah, Azemin (2014)
Objective: The aims of this study were to identify and evaluate the chemical markers of Ficus deltoidea Jack (FD) varieties namely var. deltoidea, var. trengganuensis, var. kunstleri, var. motleyana, var. intermedia, var. borneensis, var. bilobata and var. angustifolia by high performance thin layer chromatography (HPTLC) and to discriminate between the varieties based on Fourier transform infra-red (FTIR) data. Methods: Methanol extracts of eight varieties and water extracts of five varieties were subjected to HPTLC and FTIR fingerprinting analysis. Quantification of markers (vitexin and isovitexin) was performed by HPTLC. Cluster analysis of principal component analysis (PCA) and hierarchical cluster analysis (HCA) was employed to discriminate between the varieties based on their FTIR data. Results: Two markers, vitexin and isovitexin, were found in all of the varieties, but their contents were varied in the different samples. Cluster analysis (PCA and HCA) was employed to discriminate between the varieties based on their FTIR data. Clear separation between the methanol extracts of the varieties was observed, whereas the discrimination of the water extracts of the varieties showed some disparities. Conclusion: The findings indicate that HPTLC combined with FTIR coupled with chemometric analysis is a reliable analytical tool for the identification and discrimination of FD varieties.